Application of demand side management strategies to reduce energy consumption in university buildings - Hamidi, Najaatul Farihah (2015)
Demand Side Management (DSM) refers to actions that change the quantity or pattern of electrical energy consumed by end users to change its load profile. There are many available DSM measures that can be implemented, however this thesis analyses the effects of two DSM methods as strategic options to reduce energy consumption in university buildings, specifically the Faculty of Electrical Engineering at Universiti Teknologi Malaysia, Johor. The first considered option is the combination of peak clipping and load shifting, which is the process of shifting clipped peak loads away from peak periods to off-peak periods. This thesis addresses the challenge in performing peak clipping and load shifting which is determining the right time to perform peak clipping and load shifting, followed by an assessment of estimated savings in energy usage and electricity bill through these selected methods. Through careful assessment and implementation of time selection, the combined method of peak clipping and load shifting contributes up to 10% savings of energy consumption and electricity bill. Another DSM option is retrofitting which is a process that requires direct change on the existing physical or electrical system of old or already occupied buildings to achieve reduction in energy consumption and electricity bills. In this study, the potential savings by retrofitting the currently installed fluorescent T8 and T5 lighting systems with more recent LED technology in the selected buildings were examined and proved to reduce up to 64% of estimated annual energy consumption and electricity bill. Also, the payback period for which the initial investment will be recovered was evaluated to be approximately 3.03 years.